Breast cancer patients with hormone neoadjuvant bridging therapy due to asymptomatic Corona virus infection. Case report, clinical and histopathologic findings. (2020) - Pellicciaro, Marco; Granai, Alessandra Vittoria; Marchese, Gloria; Materazzo, Marco; Cotesta, Maria; Santori, Francesca; Giacobbi, Erica; Servadei, Francesca; Grelli, Sandro; Perretta, Tommaso; Meucci, Rosaria; Pistolese, Chiara Adriana; et al.
Highlights: Oncological treatments experienced a significant slowdown due to COVID-19 pandemic. Breast cancer management has changed according to scientific recommendations. Breast cancer patients with simultaneous COVID-19 could receive delayed treatments. Treatments delay could impact breast cancer staging. Abstract: Introduction: Breast cancer management during COVID-19 pandemic has changed and in case of COVID-19 patients with simultaneous neoplasia, it has been strongly recommended to treat Sars-CoV-2 infection firstly. Presentation of case: We reported a case of a 53-years-old women with early breast cancer and simultaneous asymptomatic SARS-CoV-2 infection. According to COVID-19 breast cancer recommendations she underwent hormone neoadjuvant treatment as a bridging therapy for surgery. Six months from the diagnosis, after virus eradication, patient underwent breast surgery. No SARS-CoV-2 RNA was found both in the surgical specimen and sentinel lymph node but micrometastasis were reported. During the last follow-up, the patient was in good clinical condition and started the adjuvant chemotherapy. Discussion: COVID-19 outbreak determined the publication of temporary recommendation leading to an extensive use of neoadjuvant chemotherapy in breast cancer patients. Although endocrine therapy is a mainstay in the adjuvant treatment, its role in the neoadjuvant schedule is unclear. Conclusion: Upfront awake surgery should be preferred especially in asymptomatic COVID-19 patient with early breast cancer when monitoring of tumor response is not feasible.